Optimization of solid-phase microextraction for the determination of organo-phosphorus and organo-chlorine pesticide residues in natural water near aquaculture farms / Chan Chun Foong - Chan, Chun Foong (2010)
The global shrimp farming industry had a rapid growth in the 1980s due to the high demand for shrimp. Apart from the destruction of mangroves and wetlands, the intensive operation of shrimp aquaculture deteriorated the water quality in the region. Variety of chemicals and biological products were used to prevent the outbreaks of diseases in the intensively managed shrimp ponds. Pesticides were used as disinfectands to kill unwanted organisms in the pond. SPME-GC-ECD method was developed for the determination of azinphos-ethyl, chlorphyrifos-methyl, diazinon, dichlorvos, endosulfan-I, endosulfan-II, endosulfan sulfate and malathion from water samples of shrimp aquaculture area in Manjung district, Perak. The optimum SPME method developed for GC-ECD analysis of selected analytes was found to be 30 min of extraction at 40°C under continuous stirring condition; 12 min of desorption at 270°C. No matrix modifications were applied in this study. Recoveries obtained ranged between 90.64% and 124.29% while the limit of detection (LOD) ranged from 0.01 to 5ppb for the targeted compounds.Chlorphyrifosmethyl,diazinon,endosulfan-I, endosulfan-II, endosulfan sulfate and malathion were detected from the water samples whilst azinphos-ethyl and dichlorvos were not detected.